Strategi Penanggulangan Gangguan Kawasan Konservasi Di Taman Nasional Bunaken (Studi Kasus Di Pulau Mantehage) - Engelin Seny Pomantow; Martina A. Langi; Fabiola B. Saroinsong (AGRI-SOSIOEKONOMI, 2022)
This research aims to explore the factors that cause disturbances in conservation areas and determine strategies for dealing with disturbances in Conservation Areas on Mantehage Island, Bunaken National Park, using a combination of qualitative and quantitative methods. The factors causing the disturbance were obtained through observation, questionnaires and in-depth interviews. Furthermore, a SWOT analysis is used to formulate a strategy for overcoming disturbances based on the factors that cause disturbances that have been identified. It was found that the factors causing disturbances in the Bunaken National Park area were: weak law enforcement; lack of trained human resources (Forest Police); limited facilities and supporting infrastructure; and the economic limitations of the local population. Based on the results of the research, the strategy that can be used is the SO Strategy, which uses all the strengths of the organization to take advantage of opportunities. The strategy that can be used is the development of conservation through the protection and enhancement of the conservation of the TNB area by coordinating with communities, groups, institutions and government and developing a conservation partnership program on Mantehage Island through tourism development.